2016
DOI: 10.17536/jgcgr.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a treatment for gambling disorder: Current directions and issues

Abstract: Mindfulness is a form of meditation that derives from Buddhist practice and is one of the fastest growing areas of psychological research. Studies investigating the role of mindfulness in the treatment of behavioral addictions have, to date, primarily focused on gambling disorder. Recent pilot studies and clinical case studies have demonstrated that weekly mindfulness therapy sessions can lead to clinically significant change among individuals with gambling problems. This purpose of this paper is to appraise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Examples of such interventions might include mindfulness-based group interventions because they are able to reduce urgency and increase perseverance (the two impulsivity facets shown to influence gambling behaviours in the current study) in adolescents with emotion regulation difficulties 90 . These interventions can help gamblers transfer the locus of control for stress from external conditions (i.e., feedback-related gambling) to attentional resources and reduce salience and myopic focus on rewards (i.e., by undermining the intrinsic value that gamblers assign to potential wins) 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such interventions might include mindfulness-based group interventions because they are able to reduce urgency and increase perseverance (the two impulsivity facets shown to influence gambling behaviours in the current study) in adolescents with emotion regulation difficulties 90 . These interventions can help gamblers transfer the locus of control for stress from external conditions (i.e., feedback-related gambling) to attentional resources and reduce salience and myopic focus on rewards (i.e., by undermining the intrinsic value that gamblers assign to potential wins) 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the emerging empirical evidence [30][31][32][33][34][35][36][37][38][39][40] as well as the general consensus of clinicians, researchers, and the general public, it is concluded that MBIs have the potential to play an important role in psychiatric treatment settings as well as in applied psychological settings more generally. However, due to the rapidity at which mindfulness has been taken out of its traditional Buddhist setting, and what is possibly evidence of media and/or scientific hype concerning the potency of mindfulness [5], it is recommended that future research seeks to (i) consolidate and replicate research findings, (ii) assess the maintenance of outcomes over longer time periods, (iii) investigate potential adverse effects, (iv) fully control for potential performance bias in MBI intervention studies, (v) formulate comprehensive training and supervision curricula -that are informed by the traditional meditation literature -for secular MBI instructors, and (vi) investigate the Buddhist position that sustainable improvements to mental (and spiritual) health typically require consistent daily mindfulness practice over a period of many years (i.e., they do not arise after attending eight two-hour classes with some self-practice in between).…”
Section: Does the Evidence Match The Momentum?mentioning
confidence: 59%
“…As a consequence of these findings, both the American Psychiatric Association (US) and the National Institute for Health and Care Excellence (UK) advocate the use of MBCT in the treatment of recurrent depression in adults [3]. There is also preliminary evidence that supports the use of MBIs in the treatment of a broad range of mental health issues including (but not limited to) schizophrenia-spectrum disorders, addiction disorders (both chemical and behavioral), bipolar disorder, post-traumatic stress disorder, eating disorders, and anger dysregulation [33][34][35].…”
Section: Does the Evidence Match The Momentum?mentioning
confidence: 99%
“…Another approach with potential for use as a communitylevel preventative interventional strategy for reducing adolescent gambling is mindfulness, which has been the subject of increased empirical attention in recent years (Sapthiang et al 2018). Mindfulness is a form of meditation that involves cultivating present moment awareness as a means of increasing perceptual distance from gambling urges, as well as from distressing emotions and maladaptive cognitive processes more generally (Griffiths et al 2016). Furthermore, the calm states elicited through mindfulness practice can substitute the need for gambling-related sensation seeking, as well as the desire to experience mood modification and states of elation (Shonin et al 2013).…”
Section: Community-level Health Promotion Approachesmentioning
confidence: 99%
“…Research has shown that mindfulness can be an effective preventative and treatment strategy for problem gambling (Shonin et al 2014;Griffiths et al 2016) as well as other forms of behavioural addiction in adults (Van Gordon et al 2016. Research also demonstrates that mindfulness is an accessible and effective means of addressing various behavioural and addiction problems in adolescents and children (Shonin et al 2012).…”
Section: Community-level Health Promotion Approachesmentioning
confidence: 99%